1975
DOI: 10.2151/jmsj1965.53.1_33
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Analysis of Planetary Waves in the Summer Stratosphere and Mesosphere

Abstract: An analysis was made of planetary-scale variations of temperature and wind fields in the summertime stratosphere and mesosphere by the use of meteorological rocket and satellite observations.From the vertical time-section analysis of temperature and wind at Cape Kennedy (28N, 81W) and other rocket stations in subtropics of the Northern Hemisphere, it is found that the oscillation with a period of about 15 days is predominant above 30 km.To describe the nature of wind and temperature oscillation in more detail,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Observations of an eastward traveling wave 2 with a period of ∼10-20 days in the Southern Hemisphere stratosphere in winter and spring were also reported by Venne (1980), Mechoso and Hartman (1982), Venne andStratford (1979, 1982), Prata (1984), Mechoso et al (1988), Hirota (1988), Shiotani et al (1990), Manney et al (1991), Fishbein et al (1993), to mention a few. Some westward propagating free Rossby waves have also been observed (Rodgers, 1976;Hirota, 1975Hirota, , 1976Mechoso and Hartmann, 1982;Hirota and Hirooka, 1984). It was suggested that the source of these eastward propagating waves is instability associated with their relation to the seasonal evolution of the mean zonal winds field (Hirota, 1976;Hatmann, 1979Hatmann, , 1983Hirota et al, 1990;Shiotani et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Observations of an eastward traveling wave 2 with a period of ∼10-20 days in the Southern Hemisphere stratosphere in winter and spring were also reported by Venne (1980), Mechoso and Hartman (1982), Venne andStratford (1979, 1982), Prata (1984), Mechoso et al (1988), Hirota (1988), Shiotani et al (1990), Manney et al (1991), Fishbein et al (1993), to mention a few. Some westward propagating free Rossby waves have also been observed (Rodgers, 1976;Hirota, 1975Hirota, , 1976Mechoso and Hartmann, 1982;Hirota and Hirooka, 1984). It was suggested that the source of these eastward propagating waves is instability associated with their relation to the seasonal evolution of the mean zonal winds field (Hirota, 1976;Hatmann, 1979Hatmann, , 1983Hirota et al, 1990;Shiotani et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Observations of an eastward traveling wave 2 with a period of ∼10-20 days in the Southern Hemisphere stratosphere in winter and spring were also reported by Venne (1980), Mechoso and Hartman (1982), Venne andStratford (1979, 1982), Prata (1984), Mechoso et al (1988), Hirota (1988), Shiotani et al (1990), Manney et al (1991), Fishbein et al (1993), to mention a few. Some westward propagating free Rossby waves have also been observed (Rodgers, 1976;Hirota, 1975Hirota, , 1976Mechoso and Hartmann, 1982;Hirota and Hirooka, 1984). It was suggested that the source of these eastward propagating waves is instability associated with their relation to the seasonal evolution of the mean zonal winds field (Hirota, 1976;Hatmann, 1979Hatmann, , 1983Hirota et al, 1990;Shiotani et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Houghton argued that if planetary waves in either the winter or the summer hemisphere were controlling the mean meridional circulation, then the summer mesopause temperature, which is particularly sensitive to the strength of the mean meridional circulation, should fluctuate in response to the level of planetary wave activity. That such correlations were not found using either the Nimbus 6 pressure modulated radiometer data of Curtis et al [1974] or the Nimbus 5 selective chopper radiometer data analyzed by Hirota [1975Hirota [ , 1976 led Houghton to conclude that planetary waves are not the primary vehicle for the transport of momentum into the middle atmosphere. Planetary waves can also be excluded from consideration because observations indicate (see Figure 5) that mesospheric momentum sources are required to reverse the vertical shear of the mean zonal wind in both winter and summer hemispheres, whereas quasi-stationary planetary waves cannot propagate through regions of easterly mean winds [Charney and Drazin, 1961].…”
Section: Introductionmentioning
confidence: 99%